Endovascular myocardial revascularization in a patient after transcatheter aortic valve implantation: a case report - Vasiliev, D. K.; Arablinsky, N. A.; Zamyatin, R. A.; Shukurov, F. B.; Feshchenko, D. A.; Taliuridze, M. T. (Kardiovaskuli͡a︡rnai͡a︡ terapii͡a︡ i profilaktika, 2025)
Transcatheter aortic valve implantation (TAVI) is an effective and safe method for treating aortic stenosis (AS), especially in patients at high surgical risk. With the improvement of the quality and increase in life expectancy of the population, comorbid patients with critical AS will increasingly be encountered in practice, for whom TAVI will be the main method of surgical treatment. Despite the achieved successes in the management of patients with cardiovascular diseases, their cotinuous progression can lead to de novo atherosclerotic lesions or restenosis in the previously stented coronary segment. The design of prosthetic aortic valves used in TAVI can impose a number of technical limitations when repeated coronary interventions are necessary. This article presents a case of successful endovascular treatment of multivessel coronary artery disease guided by intravascular coronary flow assessment in a comorbid patient after TAVI.